A Multi-institutional Study of Prevalence and Clinicopathologic Features of Non-invasive Follicular Thyroid Neoplasm with Papillary-like Nuclear Features (NIFTP) in Korea - Ja Yeong Seo; Ji Hyun Park; Ju Yeon Pyo; Yoon Jin Cha; Chan Kwon Jung; Dong Eun Song; Jeong Ja Kwak; So Yeon Park; Hee Young Na; Jang-Hee Kim; Jae Yeon Seok; Hee Sung Kim; et al. (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background In the present multi-institutional study, the prevalence and clinicopathologic characteristics of non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) were evaluated among Korean patients who underwent thyroidectomy for papillary thyroid carcinoma (PTC). Methods Data from 18,819 patients with PTC from eight university hospitals between January 2012 and February 2018 were retrospectively evaluated. Pathology reports of all PTCs and slides of potential NIFTP cases were reviewed. The strict criterion of no papillae was applied for the diagnosis of NIFTP. Due to assumptions regarding misclassification of NIFTP as non-PTC tumors, the lower boundary of NIFTP prevalence among PTCs was estimated. Mutational analysis for BRAF and three RAS isoforms was performed in 27 randomly selected NIFTP cases. Results The prevalence of NIFTP was 1.3% (238/18,819) of all PTCs when the same histologic criteria were applied for NIFTP regardless of the tumor size but decreased to 0.8% (152/18,819) when tumors ≥1 cm in size were included. The mean follow-up was 37.7 months and no patient with NIFTP had evidence of lymph node metastasis, distant metastasis, or disease recurrence during the follow-up period. A difference in prevalence of NIFTP before and after NIFTP introduction was not observed. BRAFV600E mutation was not found in NIFTP. The mutation rate for the three RAS genes was 55.6% (15/27). Conclusions The low prevalence and indolent clinical outcome of NIFTP in Korea was confirmed using the largest number of cases to date. The introduction of NIFTP may have a small overall impact in Korean practice.